The 3rd IAAF World Coaches Conference London, United Kingdom - Apostolopoulos, N. (New Studies in Athletics, 2017)
Zusammenfassung der 3. Internationalen IAAF-Trainerkonferenz vom 7.-10.8.2017 in London. U. Hartmann (GER): Physiologic and metabolic background to endurance training - Practical consequences for science-based endurance training Panel Discussion S. Pickering (GBR): Physiologic and metabolic background to strength training - Practical consequences for science-based strength training Panel Discussion L. Seagrave (USA): Physiologic and metabolic background to speed training - Practical consequences for science-based speed training Panel Discussion Brain endurance - The brain is a perfomance limiting factor Panel Discussion